2009
DOI: 10.1007/s00586-009-1259-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results and development of heterotopic ossification in total cervical disc replacement during a 4-year follow-up

Abstract: Cervical total disc replacement (CTDR) aims to decrease the incidence of adjacent segment disease through motion preservation in the operated disc space. Ongoing data collection and increasing number of studies describing heterotopic ossification (HO) resulting in decreased mobility of implants, forced us to carefully evaluate our long-term clinical and morphological results of patients with CTDR. We present the first 54 consecutive patients treated with 65 ProdiscC TM prostheses during a 12-month period (2/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 31 publications
6
81
2
1
Order By: Relevance
“…Similar observations were verified in a number of studies, which demonstrated comparable post-operative scores at different long-term observation periods, ranging between 4 and 30 years, and irrespective of the type of prosthesis used [2][3][4][16][17][18][19].…”
Section: Long-term Follow-up Of Clinical Outcome Parameterssupporting
confidence: 81%
See 1 more Smart Citation
“…Similar observations were verified in a number of studies, which demonstrated comparable post-operative scores at different long-term observation periods, ranging between 4 and 30 years, and irrespective of the type of prosthesis used [2][3][4][16][17][18][19].…”
Section: Long-term Follow-up Of Clinical Outcome Parameterssupporting
confidence: 81%
“…Qureshi et al analysed the cost-effectiveness comparing single level TDR and ACDF and conclude also that cTDR and ACDF are cost-effective procedures, but cTDR must remain functional for at least 14 years to establish greater cost-effectiveness than ACDF [34]. The appearance of HO right up to solid fusion (Grade 4) is a well known complication in cervical total disc replacement which can affect the motion, respectively, the function of the prosthesis [31,32,35] regardless the implant-type [7,11,17,27,28,[36][37][38][39]. The progression of HO into higher grades over time was also seen in other studies [28,32].…”
Section: Adjacent Segment Degenerationmentioning
confidence: 99%
“…On the other hand, Qizhi et al [29], who used the Discover device in two-level disc surgery, found no HO after 32,4 months. Tu et al [18] reported 50 % HO with the Bryan device at a mean 19 months follow-up, and Suchomel et al [28] found high-grade HO in 63 % after 4 years with the ProDisc-C. Thus, different degrees of constraints seem to influence the development of HO, but HO also differs among devices with the same degree of constraint and in different reports concerning the same device.…”
Section: Discussionmentioning
confidence: 99%
“…Mehren et al reported an ossification rate of 49.4 % one year after implantation of disc device and suspected an even higher rate of spontaneous fusion after long-term follow-up [13]. The reported incidence of spontaneous fusion after ACDA varies from 18 % after 4 years [14] to 60 % after 5 years following implantation [15]. To minimise failures in ACDA, good implant design is required.…”
Section: Discussionmentioning
confidence: 99%